2019
DOI: 10.1055/a-0899-5118
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Insulin Degludec in Thai Patients with Diabetes Mellitus: Real-World Evidence From a Specialized Diabetes Center

Abstract: ABSTr AC TBackground Insulin degludec, an ultra-long-acting insulin analogue, has been available in Thailand since October 2016. Although clinical trial results revealed less hypoglycemia, data from real-world settings is limited especially in Asian patients. This study aimed to evaluate prospectively the real-world effectiveness, safety, quality of life (QOL) and patient satisfaction with insulin degludec among Thai patients with diabetes mellitus (DM).Methods From October 2016 to September 2017, all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Regarding the effectiveness and safety according to the study background and design, real-world data reported that switching to IDeg from basal insulins and other glucose-lowering medications showed 0.5% and 0.8% HbA1c reduction from the EUropean TREsiba AudiT (EU-TREAT) study ( n = 2550) [ 24 ] and Thai population ( n = 55) [ 20 ], respectively. Both studies also showed the reduced risks of patient-reported hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effectiveness and safety according to the study background and design, real-world data reported that switching to IDeg from basal insulins and other glucose-lowering medications showed 0.5% and 0.8% HbA1c reduction from the EUropean TREsiba AudiT (EU-TREAT) study ( n = 2550) [ 24 ] and Thai population ( n = 55) [ 20 ], respectively. Both studies also showed the reduced risks of patient-reported hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing need for real-world data to provide the necessary evidence for a broad range of patients in routine clinical practice. The real-world data of IDeg from the larger patient population, specifically for Asian patients, are limited [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…El Whoqol-Bref, consta de 26 ítems, dos preguntas generales sobre calidad de vida y satisfacción con el estado de salud, y 24 preguntas agrupadas en cuatro áreas (salud física, salud psicológica, relaciones sociales y ambiente); Todas las escalas de respuesta son de tipo Likert (0-5) (21) (22). Los puntajes de dominio se transformaron en una escala lineal de 0 a 100 siguiendo las pautas de calificación; a mayor puntuación, indica una mejor calidad de vida (23) (24) .…”
Section: Materiales Y Métodosunclassified